2017
DOI: 10.1088/2053-1583/aa604a
|View full text |Cite
|
Sign up to set email alerts
|

Deep ultraviolet emission in hexagonal boron nitride grown by high-temperature molecular beam epitaxy

Abstract: We investigate the opto-electronic properties of hexagonal boron nitride grown by high temperature plasma-assisted molecular beam epitaxy. We combine atomic force microscopy, spectroscopic ellipsometry, and photoluminescence spectroscopy in the deep ultraviolet to compare the quality of hexagonal boron nitride grown either on sapphire or highly oriented pyrolytic graphite. For both substrates, the emission spectra peak at 235 nm, indicating the high optical quality of hexagonal boron nitride grown by molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 28 publications
10
93
0
Order By: Relevance
“…4,15 The high optical quality of our hBN grown at high temperatures on highly oriented pyrolytic graphite (HOPG) has been confirmed by both spectroscopic ellipsometry and photoluminescence spectroscopy. 33,37 Using AFM we also observe hexagonal moir e patterns, consistent with the close rotational alignment of the hBN lattice and the graphite substrate. 33,39 In this paper, we present our recent results on the hightemperature PA-MBE growth of hBN monolayers with atomically controlled thicknesses for 2D applications and on the growth of significantly thicker hBN layers for potential DUV applications.…”
Section: Introductionsupporting
confidence: 62%
See 4 more Smart Citations
“…4,15 The high optical quality of our hBN grown at high temperatures on highly oriented pyrolytic graphite (HOPG) has been confirmed by both spectroscopic ellipsometry and photoluminescence spectroscopy. 33,37 Using AFM we also observe hexagonal moir e patterns, consistent with the close rotational alignment of the hBN lattice and the graphite substrate. 33,39 In this paper, we present our recent results on the hightemperature PA-MBE growth of hBN monolayers with atomically controlled thicknesses for 2D applications and on the growth of significantly thicker hBN layers for potential DUV applications.…”
Section: Introductionsupporting
confidence: 62%
“…We have already demonstrated that we can control the hBN layer coverage by adjusting the epitaxial growth temperatures for submonolayer thicknesses. 33,37 Several hBN layers were grown under the same B and active nitrogen fluxes on sapphire and HOPG substrates in the temperature range from 1390 to 1690 C. 37 At the highest growth temperatures, only a small density of hBN islands was observed and the coverage gradually increased to a complete hBN monolayer by decreasing the growth temperature. This effect has been explained by hBN sublimation at high MBE growth temperatures above 1390 C. 37 Another way to control reproducibly the hBN monolayer coverage is to change the MBE growth time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations